Policy Network: Smart Village Program in Banyuwangi Regency - Dewi Gartika; Budiman Rusli; Atik Rochaeni; Riki Satia Muharam (Iapa Proceedings Conference, 2019)
Smart Kampung is a concept of community development in a community to do something smart / wise in overcoming various problems with the ability of resources that are available efficiently in an area. Smart village aims to encourage the development of rural areas by integrating development of productive economic activities, creative and socio-cultural activities, improving public services, improving the quality of education, improving the quality of health services and alleviating poverty by utilizing the use of information and communication technology. Constraints that occur in smart village program from the network with limited quota and lack of human resources for service operators. This study aims to examine and analyze related policy networks in the implementation of the Smart Village program in Banyuwangi Regency. The theory used in this research is the Policy Network theory from Frans Van Waarden. The method used is a qualitative research method. The results of the study show that the actors involved in the implementation of the Smart Kampung program consisted of government and community elements. Research recommendations on the need for other actors involved in implementing smart village programs such as the social community, the private sector and academics.